ANALISIS FAKTOR PERILAKU KELUARGA DENGAN KEJADIAN DBD - Dian Mahanani; Kasman Lestaluhu; Notesya A. Amanupunnyo; Haesti Sembiring (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Dengue hemorrhagic fever remains a serious concern due to its relatively rapid spread and potential to cause outbreaks in various regions. The objective of this study was to analyze family behavioral factors associated with dengue hemorrhagic fever cases. A case-control study design was used. The study was conducted in the service area of the PAAL V Community Health Center in September 2025. The sample consisted of 25 cases and 25 controls, totaling 60 respondents. Total Sampling was used for sample selection. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between the frequency of draining open waste containers (p-value: 0.002) and the habit of hanging clothes (p-value: 0.034) with dengue fever cases. It is recommended that Community Health Centers (Puskesmas) educate the public through outreach activities to always cover trash bins, empty them at least once a week, raise mosquito-larva-eating fish, maintain and care for plants, and avoid the habit of hanging clothes indoors.Keywords: Dengue Fever, Frequency of Emptying Landfills, Habits of Hanging Clothes.